2015
DOI: 10.1016/j.ijscr.2014.10.093
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of isolated hydatid cyst of breast

Abstract: HighlightsHydatid cyst of the breast is very rare.It is challenging to differentiate it from other tumoral lesions of the breast as it might mimic fibroadenoma, phyllodes tumors, chronic abscesses or even carcinoma.Only few reports of breast hydatid cyst are published and majority of the reported cases have been diagnosed postoperatively as it is not possible to reach definitive diagnosis with clinical examination and radiological investigations only.In spite of being very uncommon, it should be included in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…On ultrasound, the lesion is usually indistinguishable from simple or complicated cysts [20, 21]. On MRI, it appears as a well defined cystic lesion with capsular enhancement [20, 21]. In our study, we encountered only one case of hydatid cyst in the breast and chest wall.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…On ultrasound, the lesion is usually indistinguishable from simple or complicated cysts [20, 21]. On MRI, it appears as a well defined cystic lesion with capsular enhancement [20, 21]. In our study, we encountered only one case of hydatid cyst in the breast and chest wall.…”
Section: Discussionmentioning
confidence: 83%
“…Breast is an exceedingly rare location for CE to develop and accounts for only 0.27% of all cases [20, 21]. Mammography shows vague findings and the cyst usually appears as a circumscribed mass with thin peripheral calcification, similar to a simple cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common ultrasonographic appearance in this study was a multiloculated cystic lesion with thick internal septa and echogenic materials. Similarly, ultrasonography of a breast hydatid cyst by Kumar et al revealed a thick-walled cystic lesion with floating membranes and internal echoes in the subareolar region of the right breast (17).…”
Section: Discussionmentioning
confidence: 89%
“…It might mimicked fibroadenoma, phyllodes tumors, chronic abscesses, or even carcinoma. 10 A 28-year-old woman presented with gradually progressive, painful left breast since one month duration. There was no history of injury, discharge from the nipple and family history of breast cancer.…”
Section: Discussionmentioning
confidence: 99%